An efficient exponential based integration for von Mises plasticity combined with Lemaitre damage model. (1st February 2022) - Tavoosi, Maliheh; Sharifian, Mehrzad; Sharifian, Mehrdad
Highlights: For the first time, the efficient exponential map integration is derived for the damage mechanics. The von Mises yield criterion along with the Lemaitre damage mechanics is considered. The constitutive equations are transformed into the augmented stress space. The numerical tests demonstrate the high performance of the suggested method. Abstract: In elastoplastic problems, integrating the constitutive equations decides the final state of stress and the related plastic variables. Integration based on exponential-mapping strategy is a new and promising method to fulfill the task and has not been implemented for the problems of damage mechanics yet. For the first time, here, the exponential-mapping technique is developed for the elastoplastic finite element analyses of structures combined with Lemaitre damage model. Subsequently, the associated stress-updating algorithm is presented to clearly show the process of finding stress and its pertinent variables during a nonlinear finite element analysis with the derived method. Afterwards, an extensive range of numerical tests is carried out to evaluate the performance of the suggested formulae including verification, precision, convergence rate, and efficiency investigations. Consequently, the outcomes demonstrate a high level of performance by the new algorithm to solve the fundamental elastoplastic equations and update the stress in nonlinear finite element analyses.